THE EFFECT OF DIFFERENTIATED LEARNING ON CRITICAL THINKING SKILLS OF GRADE VIII STUDENTS ON HUMAN EXCRETORY SYSTEM MATERIAL - Alifa Tanzila Meiviana; Leo Moh. Taufik; Nurwanti Fatnah (Jurnal IPA Terpadu, 2024)
This research aims to analyze the students' critical thinking skills on the human excretory system material through differentiated learning based on content and process. There are three elements in the differentiated learning that are considered in this research; the student interest, the profile, and the readiness to learn. This research used quasi experimental methods with a non-equivalent control group research design. The sample amounted up to 60 students from two classes : 30 experimental class students and 30 control class students. The instrument used for the critical thinking skills test is 15 multiple-choice questions with C4 and C5 cognitive processes. The differentiated learning instruments are in the form of diagnostic assessments and formative assessments. Data processing was carried out using non-paramatric statistic Wilcoxon Test and N-Gain Test. The results showed that the influence of differentiated learning on the students' critical thinking skills on human excretory system material indicated by the Asymp value. Sig 0.000. A total of 30 students had no negative difference and increased by 25%. Applied differentiated learning had an effect size of 42% or 0.42 with the category "medium".